Cytoreductive surgery and HIPEC improve survival compared to palliative chemotherapy for biliary carcinoma with peritoneal metastasis: A multi-institutional cohort from PSOGI and BIG RENAPE groups. Issue 9 (September 2018) - Amblard, I.; Mercier, F.; Bartlett, D.L.; Ahrendt, S.A.; Lee, K.W.; Zeh, H.J.; Levine, E.A.; Baratti, D.; Deraco, M.; Piso, P.; Morris, D.L.; Rau, B.; et al.
Abstract: Background: Peritoneal metastasis from biliary carcinoma (PMC) is associated with poor prognosis when treated with chemotherapy. Objective: To evaluate the impact on survival of cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC), and compare with conventional palliative chemotherapy for patients with PMC. Material and methods: A prospective multicenter international database was retrospectively searched to identify all patients with PMC treated with a potentially curative CRS/HIPEC (CRS/HIPEC group). The overall survival (OS) was compared to patients with PMC treated with palliative chemotherapy (systemic chemotherapy group). Survival was analyzed using Kaplan-Meier method and compared with Log-Rank test. Results: Between 1995 and 2015, 34 patients were included in the surgical group, and compared to 21 in the systemic chemotherapy group. In the surgical group, median peritoneal cancer index was 9 (range 3–26), macroscopically complete resection was obtained for 25 patients (73%). There was more gallbladder localization in the surgical group compared to the chemotherapy group (35% vs. 18%, p  = 0.001). Median OS was 21.4 and 9.3 months for surgical and chemotherapy group, respectively ( p =0.007). Three-year overall survival was 30% and 10% for surgical and chemotherapy group, respectively. Conclusion: Treatment with CRS and HIPEC for biliary carcinoma with peritoneal metastasis is feasible and may provide survival benefit when compared to palliative chemotherapy.